Better off at home? Effects of a nursing home admission on costs, hospitalizations and survival - Pieter Bakx; Bram Wouterse; Eddy van Doorslaer; Albert Wong (Tinbergen Institute, 2018)
Aging-in-place policies substitute home care for nursing home admissions (NHA). They appear to be a win-win by keeping public spending in check and being in line with personal preferences, but have hitherto not been evaluated. We study the impact of NHA eligibility using Dutch administrative data and exploiting variation between randomly assigned assessors in their tendency to grant admission. The impact on mortality is zero, but with considerable effect heterogeneity. Moreover, aging-in-place policies come at the cost of increased curative care, especially hospital admissions, and do not reduce total healthcare spending, suggesting they may not be a win-win after all.
Keywords: C26; I10; 330; long-term care; policy evaluation; instrumental variables